Issues and Challenges with Blockchain: A Survey - Meva, Divyakant (International Journal of Computer Sciences and Engineering, 2018)
Blockchain is one of the latest trends in Information Technology domain. It has changed a way of thinking for IT professional. Companies are focusing on implementation of blockchain with their services to ensure security and reliability. Still they are facing challenges and issues for development and implementation of blockchain based services. This paper discusses those issues and challenges to be considered in development and implementation.